Eliminating the dichotomy between theory and practice in talent identification and development: Considering the role of psychology - Abbott, A.; Collins, D. (Journal of Sports Sciences, 2004)
It is acknowledged that appropriate support and training are essential if talented individuals are to fulfil their potential. The early identification of talented athletes is an increasingly important consideration for researchers and practitioners alike. Once talented individuals have been detected, crucial but limited support resources can be optimally deployed to ensure that their needs are met and that their gifts are developed. However, there is considerable disagreement among experts on what talent is, and which factors can reliably be used within talent identification processes. This paper explores prerequisites to success in sport, and the comparative efficacy of employing these prerequisites within talent identification schemes. It is proposed that talent needs to be reconceptualized so that talent identification and talent development processes are perceived to be dynamic and interrelated. Additionally, the need to place greater emphasis on the capacity of a child to develop in sport and the psychological factors that underpin this process is highlighted. To this end, it is advocated that talent identification and development schemes, while emphasizing the multidimensional nature of talent, need to recognize the essential role of psychology in the ability of individuals to fulfil their sporting potential.